(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This paper is focused on marking a balance in AI and EQ. The paper combines both theoretical assumptions and practical examples. The general idea is that a customer journey is crucial. Reaffirming the belief that the prime pillar in a business process of production plan and marketing efforts is a customer centric culture. Transformation of personalised data connect to AI necessitated with the changing times. It has enabled easy capturing of big data. Each industry maximises their business potential with this data. A big dream of converting customer base gradually to big data, as customers modified to consumers. Eventually directing the need to install CRM solutions. Considering the potential, the race of customised industry specific solution providers, multiplied. They designed plug and play, quick to install methods enhancing digitization from conventional tiring and delayed data communications. This was in 1990 and we heard CRM innovation building success stories. A new role of CTO emerged in the company. The tools of analysing, freedom to add algorithm. Automated instant responsive communications from good old phone support with waiting and holding changed to surprised customer satisfaction. In this process, we discovered a new glitch. The CRM technology convinced to reform landscapes of speed and engagement to forfeiture of human connect. Direct voice communication filled with an elementary human need of “empathy” vanished. Contactibility challenges resulted in high grade of frustrations for customers. Just when companies thought Customer experience upgraded, harsh truth announced CRM as a imperceptible. Worry of capturing data resolved, however only in numbers, concluding CRM as single entry, one way.To find the balance of AI and EQ for various industries who are misled into digitization. CRM was a desolate trail in proving the true essence of the connection between the touch points and VOC. Many companies struggled to tackle on either side of the drift to gain the equilibrium. To reduce volatility, in these challenging and unexpected times, we use the best tools of technology. The insight of every walk-in customer is a gold mine. This increases a three-way journey of communication, which is essential at the operations and front office levels.CUSTOMER BRAND OPERATIONS OWNERWe must create a relay, so the brand’s most important leaders, operational heads can hear it. Aren’t they curios, at every stage The leaders must be alert and want to resolve the customers issues While customers can also communicate painlessly. Touchpoints have a voice (VOE), its validated only if it is communicated received by the leaders too. The data is at every level, all service feedback calls, customers talk to their best heroes in the company or notify the gap occurred due to erroneous communications. Customers are vocal about their experiences, which is good for business. They want speed and personalized resolution.